Education Policies for Enhancing Professional Competence in Elementary School Teachers - Fenti Farleni; Dewi Nancy Shabatini; Encep Syarifudin; Cucu Atikah (Journal of Education Reseach and Evaluation, 2024)
The quality of education is influenced by many elements, such as the quality of teachers, efforts to increase equity, curriculum design, provision of adequate facilities and infrastructure, and the creation of a conducive learning environment. Furthermore, government legislation facilitates improvements in these components. In optimizing the achievement of educational goals, it is necessary to form a cadre of educators who are capable and able to demonstrate exemplary performance. This research aims to analyze educational policies to increase the professional competence of elementary school teachers. This type of research is qualitative. This research uses a descriptive qualitative approach. The data obtained in this research can be classified into primary data and secondary data. The main data sources for this research consist of critical school leaders and certified teachers. Secondary data refers to a comprehensive collection of materials available in a research environment, including diverse formats such as letters, images, and procedural documents related to a research investigation. The data analysis technique uses qualitative analysis using the theoretical framework proposed by Milles and Huberman. The results of this research show that educational policy analysis is to improve the quality of the teaching profession, legal sources increasingly cover the position of teachers, and professional teacher education improves the position and professionalism of teachers.